IMPLEMENTASI PEMBELAJARAN FIQIH DENGAN MENGGUNAKAN METODE DEMONSTRASI DI BETONG JUNIOR KHALIFAH SCHOOL - Rosvita Herdiana Riyanti Br Ginting; Hasrian Rudi Setiawan (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Islamic religious education is vital for all muslims who are muslims. One is the fiqih lesson, which takes an important part in the daily lives of every Muslim. By the method of demonstration gave a clearer picture and could readily be seen by paying attention to the teacher's practice and by giving a verbal explanation. The purpose of this study: 1. Describe the implementation of fiqih learning by using demosntration methods at betong junior khaliffah schoon. 2. Describe the Benefits of Implementing Fiqh Learning Using the Demonstration Method at the Betong Junior Khalifah School. The method used in this study is a qualitative method with a qualitative form of description, hence the data-gathering technique used was interviews, observation and documentation. The rtesults: 1. By the observation the author made at the junior caliph school that educators or teachers had already performed the ritual of prayer using demonstration methods. And the goals to be achieved were delivered after the tahities. 2. After methods of demonstration were implemented on prayer materials in fiqih subjects, then educators gave concrete understanding to learners. This has been reinforced by documenting ongoing demonstrations as well as by direct interviews.